Trace Metal Leaching from Cookware Locally Fabricated from Scrap Metal: A Case Study of Ntungamo District, Uganda - Habimaana, Samuel; Gumisiriza, Hannington; Birungi, Grace (American Journal of Analytical Chemistry, 2022)
Abstract Heavy metal exposure remains a significant public health problem, particularly in sub-Saharan Africa where use of artisanal cookware made from recycled metallic materials is still common. In this study, the effect of cookware composition, cleaning material, heating duration and temperature on metal migration from different cookware, including artisanal pans was investigated. Trace element concentrations were determined with Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Locally fabricated cookware leached the highest levels of metals, where the levels of Pb (9.00 ± 0.80 × 10−2 mg/l), Al (11.40 ± 0.02 × 10−2 mg/l), Cd (5.80 ± 0.30 × 10−2 mg/l), Cr (6.60 ± 0.03 × 10−2 mg/l) and Ni (3.00 ± 0.01 × 10−2 mg/l) were above the WHO permissible limits of heavy metals for drinking water. Steel wire was the most aggressive cleaning material to the cookware surfaces, followed by sand and then ash. For cookware heated at 100˚C and above, an exponential relationship between temperature and the migration of Al, Pb and Cd was observed. The findings revealed heavy metal exposure from cookware usage, which poses potential health risks to the population. There is need for policies and civic education to minimize this exposure.
Keywords: Local Fabrication; Cookware; Metal Leaching; Scrap Metal; Uganda